Dinamika Kemasaman dan Status Ionik pada Tanah Gambut yang diberi Berbagai Jenis Abu - Saputra, Riza Adrianoor; Fatimah, Siti; Noor, Muhammad; Jumar, Jumar (Agrotechnology Research Journal, 2024)
The aim of this research is to determine the effects of various types of ash on the acidity and ionic status of peat soil, as well as to investigate the relationship between soil acidity and the ionic status of peat soil treated with these different types of ash. The research employed a one-factor completely randomized design (CRD). The factor studied was the type of ameliorant, consisting of four levels: a0 = no ameliorant, a1 = rice husk ash, a2 = sawdust ash, and a3 = empty oil palm bunch ash. Each treatment was replicated five times, resulting in a total of 20 experimental units. The results indicated that the application of ash significantly affected the acidity (pH), redox potential (Eh), Electrical Conductivity (EC), and Cation Exchange Capacity (CEC) of peat soil at various observation times. The relationships observed were as follows: soil pH and Eh exhibited a moderate negative correlation (r = -0.522 at three  months after treatment), Eh and EC showed a strong negative correlation (r = -0.643 at three months after treatment), EC and CEC had a positive correlation (r = 0.620 at 18 months after treatment), and CEC with pH demonstrated a positive correlation (r = 0.550 at 12 months after treatment). The most effective ameliorant was found to be empty oil palm bunch ash (a3), followed by sawdust ash (a2).